A new species of Hexabdella (Acari: Bdellidae) from Brazil - Hernandes, Fábio A.; Daud, Rodrigo D.; Feres, Reinaldo J.f. (Zootaxa, 2007)
A new species of the genus Hexabdella Van der Schyff, Theron & Ueckermann, Hexabdella cinquaginta sp.n. is herein described, representing the second species of the family Bdellidae from the neotropical region. It can be distinguished from H. singula by its lobed striae on lateral margins of hysterosoma and by the leg chaetotaxy. A key to species of the genus is presented.